Employment- wage decisions in the insider-owned firm - Victor Polterovich (Bank of Finland, Institute for Economies in Transition (BOFIT), 2000)
The paper is intended to explain low sensitivity of employment decisions observed in transition economies where insider ownership prevails and capital markets are not highly developed.We introduce a stability concept for employment levels of a labor-managed firm and prove that there exists a segment of stable employment levels. If a level belongs to the interior of the segment then the firm keeps the same labor input level under any not too large changes. By contrast, the wage rate is responsive.Only the firms on the boundaries of the segment may reconsider employment decisions. Deterioration of market conditions entails decreasing labor inputs for firms with much excess labor and, the same time, increases employment for firms with low levels of labor input.This creates inter-firm flows of workforce and restrains the rise of total unemployment.Stability segments exist also for firms where employment-wage decisions are made by bargaining between workers and managers, and may exist for manager-dominated firms as well. Several concepts of labor hoarding are discussed.
URN:NBN:fi:bof-201408072014
Keywords: 330